2013
DOI: 10.1128/ec.00370-12
|View full text |Cite
|
Sign up to set email alerts
|

Pbp1 Is Involved in Ccr4- and Khd1-Mediated Regulation of Cell Growth through Association with Ribosomal Proteins Rpl12a and Rpl12b

Abstract: The Saccharomyces cerevisiae Pbp1 [poly(A)-binding protein (Pab1)-binding protein] is believed to be involved in RNA metabolism and regulation of translation, since Pbp1 regulates a length of poly(A) tail and is involved in stress granule (SG) formation. However, a physiological function of Pbp1 remains unclear, since the pbp1⌬ mutation has no obvious effect on cell growth. In this study, we showed that PBP1 genetically interacts with CCR4 and KHD1, which encode a cytoplasmic deadenylase and an RNA-binding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…The yeast ortholog of ATXN2, Pbp1, is also an interactor of poly(A) binding protein and modulates RNA processing, relocalizing to SG in periods of cell stress [38, 39]. Recent reports showed a role of Pbp1 in the regulation of mTOR signals that control translation [40, 41] and implicated it in the stress-dependent translational regulation of precursor proteins destined to mitochondria [42].…”
Section: Introductionmentioning
confidence: 99%
“…The yeast ortholog of ATXN2, Pbp1, is also an interactor of poly(A) binding protein and modulates RNA processing, relocalizing to SG in periods of cell stress [38, 39]. Recent reports showed a role of Pbp1 in the regulation of mTOR signals that control translation [40, 41] and implicated it in the stress-dependent translational regulation of precursor proteins destined to mitochondria [42].…”
Section: Introductionmentioning
confidence: 99%
“…pbp1 mutation is dependent on another deadenylase, Pan2. A previous report also showed that pbp1Δ suppresses the temperature-sensitive phenotype associated with ccr4Δ mutant (Kimura et al, 2013). Thus, we examined whether pbp1Δ affects the growth defect of puf5Δ at high temperature.…”
Section: Puf5 Regulates Lrg1 Mrna Independently Of Deadenylationmentioning
confidence: 89%
“…Further studies have shown deletions of pbp1 to suppress defects and or/lethality associated with mutations of other key genes (Kimura and Irie, 2013; Mangus et al, 1998; Woolstencroft et al, 2006). This is particularly interesting in light of the lack of severe phenotypes seen in pbp1 mutants (Kimura and Irie, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have shown deletions of pbp1 to suppress defects and or/lethality associated with mutations of other key genes (Kimura and Irie, 2013; Mangus et al, 1998; Woolstencroft et al, 2006). This is particularly interesting in light of the lack of severe phenotypes seen in pbp1 mutants (Kimura and Irie, 2013). Given Pbp1’s role in regulating HO translation (Tadauchi et al, 2004), and pheromone production (Park et al, 2016), it is a formal possibility that PbpA is required for proper expression and/or translation of mating type ( MAT ) genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation